Analysis of maternal death autopsies from the nationwide registration system of maternal deaths in Japan. (1st February 2018) - Hasegawa, Junichi; Wakasa, Tomoko; Matsumoto, Hiroshi; Takeuchi, Makoto; Kanayama, Naohiro; Tanaka, Hiroaki; Katsuragi, Shinji; Nakata, Masahiko; Murakoshi, Takeshi; Osato, Kazuhiro; Nakamura, Masamitsu; Sekizawa, Akihiko; et al.
Abstract: Objective: To clarify the necessity for and problems related to autopsy for determining the cause of maternal death in Japan. Methods: Women who died during pregnancy or within a year after delivery were analyzed by the Maternal Death Exploratory Committee between 2012 and 2015 in Japan. Maternal deaths were analyzed to verify the requirement of autopsy in cases in which autopsy was performed and the need for autopsy in cases in which it was not performed. Results: Among the 49 cases performed autopsy, the final diagnosis was compatible with the clinical course in 24 cases, while the autopsy diagnosis was incompatible with the clinical course in 13 cases. In two cases, the final diagnosis was based on the clinical course, but an autopsy could exclude other possible causes. In three cases, no exact cause of maternal death was identified after autopsy. On the other hand, in cases without an autopsy, the final diagnosis was made using ante-mortem operating findings and surgical specimens in twenty-one cases. Though, thirty-one cases were estimated diagnosis based on post-mortem imaging or ante-mortem examinations, the exact original cause of death was not determined in 25 cases, and the cause of death could not be identified in eight cases without autopsy. Conclusion: Because in most cases the autopsy provides an exact cause of death, the necessity of autopsies should be more widely accepted in Japan.